1990
DOI: 10.7883/yoken1952.43.101
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Antibodies Against Human Immunodeficiency Virus, Human T-Cell Lymphotropic Virus Type 1, Hepatitis B Virus, Hemorrhagic Fever With Renal Syndrome Virus and Chlamydia in Tonga and Western Samoa

Abstract: SUMMARY:Among the populations of Tonga and Western Samoa, serum antibodies against human immunodeficiency virus or hemorrhagic fever with renal syndrome virus were not detected (0/904 and 0/192). No serum samples were considered to be positive for antibody against human T-cell lymphotropic virus type 1 (0/527). Hepatitis B antigen and antibody were found in 4% (8/192) and 47% (90/192), respectively.Chlamydia trachomatis IgG and C. psittaci IgG antibodies were detected in 39% (75/192) and 47% (91/192), respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…HIV. The majority of studies up to the early 2000s found an HIV prevalence of zero to <1% among Pacific Islanders, including men and pregnant and nonpregnant women (Table 2) [6,31,32,34,[54][55][56][57][58][59][60][61]. The highest HIV prevalence was found among men and women attending an emergency department in PNG (18%) followed by FSW (10%) who had more than a 10-fold higher HIV prevalence than the general population [40,62].…”
Section: Prevalence and Incidence Data On Stis Among Pacific Islander...mentioning
confidence: 99%
See 3 more Smart Citations
“…HIV. The majority of studies up to the early 2000s found an HIV prevalence of zero to <1% among Pacific Islanders, including men and pregnant and nonpregnant women (Table 2) [6,31,32,34,[54][55][56][57][58][59][60][61]. The highest HIV prevalence was found among men and women attending an emergency department in PNG (18%) followed by FSW (10%) who had more than a 10-fold higher HIV prevalence than the general population [40,62].…”
Section: Prevalence and Incidence Data On Stis Among Pacific Islander...mentioning
confidence: 99%
“…Since the early 2010s, more studies reported using a rapid antibody/antigen combination as the initial test followed by additional rapid antibody tests if the first result was positive [6,37,41,42,47,48,63,64]. Foreign research efforts significantly expanded the capabilities for HIV testing in PICTs given the cost and limited laboratory and personnel resources in most PICTs [6,[55][56][57].…”
Section: Historical and Current Approaches To Sti Testing In Pictsmentioning
confidence: 99%
See 2 more Smart Citations